(untitled) (Global Journal of Human-Social Science, 2013)
This paper deals with the travails of national security in the context of democracy and urbanism. It argues that the securitization of democracy has undermined democratic freedoms. Central to the arguments is that the constrain of democracy in Africa has been the reduction of its principles to serve sentiment of the developing community. It further argues that democracy should be seen as an essentially contested concept, not in ways that denies its core values but that recognize its pluralism. It is this pluralism of democracy that creates the lacuna that in many cases contravene some basic security values such as force and precision particularly in city centers. Democracy in Nigeria attempt compromising security into face saving agenda. This constitutes threat to its essence and commitment to order and obedience. This unfortunately caught most African police napping helplessly. The paper concludes with some ways forward.